Nomenclatural studies toward a world catalog of Diptera genus-group names. III. Christian Rudolph Wilhelm Wiedemann - Evenhuis, Neal L.; Pont, Adrian C. (Zootaxa, 2013)
The Diptera genus-group names of Christian Rudolph Wilhelm Wiedemann are reviewed and annotated. A total of 50 available genus-group names in 25 families of Diptera are listed alphabetically for each name giving author, year and page of original publication, originally included species, type species and method of fixation, current status of the name, family placement, and a list of any emendations of it that have been found in the literature. Remarks are given to clarify nomenclatural or taxonomic information. A biography of Wiedemann is given with discussion of his works and his relationships with contemporaries. In addition, an index is given to all the species-group names of Diptera proposed by Wiedemann (1,775 of which 1,698 are available) with bibliographic reference to each original citation. An appendix gives a complete bibliography of all the known writings by Wiedemann, non-zoological as well as zoological. The following type species is designated herein: Eristalis chrysopygus Wiedemann, 1819 for Pachycephalus Wiedemann, 1830, by present designation [Syrphidae]. Corrected or clarified type-species and methods of typification are given for: Colax Wiedemann, 1824 [Nemestrinidae]; Cyphomyia Wiedemann, 1819 [Stratiomyidae]; Philoliche Wiedemann, 1821 [Tabanidae]; Ropalomera Wiedemann, 1820 [Ropalomeridae]; Timia Wiedemann, 1824 [Ulidiidae]. Acting as First Reviser, the following correct original spelling for multiple original spellings is selected: Maekistocera Wiedemann, 1820 [Tipulidae]. A previous First Reviser action for multiple original spellings missed by other workers is given for the following: Rhaphiorhynchus Wiedemann, 1821 [Pantophthalmidae]. The following nominal genera enter into new synonymies: Ceratophyia Osten Sacken, 1858 of Ceratophya Wiedemann, 1824, n. syn. [Syrphidae]; Epopter Wiedemann, 1830 of Sphecomyia Le Peletier & Serville, 1825, n. syn. [Syrphidae]; Melophaga Wiedemann, 1830 of Melophagus Latreille, 1802, n. syn. [Hippoboscidae]; Midas Latreille, 1797 of Mydas Fabricius, 1794, n. syn. [Mydidae]; Nemestrina Latreille, 1809 of Nemestrinus Latreille, 1802, n. syn. [Nemestrinidae]; Pangonia Latreille, 1809 of Pangonius Latreille, 1802, n. syn. [Tabanidae]; Scatophaga Wiedemann, 1828 of Scathophaga Meigen, 1803, n. syn. [Scathophagidae]; Threneste Wiedemann, 1830 of Penthetria Meigen, 1803, n. syn. [Bibionidae].